2020
DOI: 10.1080/15389588.2020.1810245
|View full text |Cite
|
Sign up to set email alerts
|

Understanding users’ characteristics in the selection of vehicle seating configurations and positions in fully automated vehicles

Abstract: Objective: To understand which users' characteristics influence their preferences in the selection of vehicle seating configurations and positions across different traveling scenarios involving a fully automated vehicle (FAV). Methods: Participants (n ¼ 730) completed an online survey in which they were asked to imagine traveling in a FAV across three hypothetical scenarios. Participants were asked to select between five different seating configurations and four positions for each scenario and about their anth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Despite the potential for automated vehicles to revolutionise personal transportation, especially for those who cannot currently hold a driver's license, automated vehicle manufacturers are currently faced with concerns associated with trusting a system that can function completely free of human input (Bansal et al, 2016;Haboucha et al, 2017;Kyriakidis et al, 2015;Lopez-Valdes et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the potential for automated vehicles to revolutionise personal transportation, especially for those who cannot currently hold a driver's license, automated vehicle manufacturers are currently faced with concerns associated with trusting a system that can function completely free of human input (Bansal et al, 2016;Haboucha et al, 2017;Kyriakidis et al, 2015;Lopez-Valdes et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Most passive safety tests are performed with a specifically determined position of the seat, and the ATD (anthropomorphic test device) dummies are carefully seated in order to ensure the repeatability of the tests. However, facing the development of smart vehicles which, in theory, requires minimal driver input, allowing various positions of the seat, an extensive investigation into this matter is justified [1][2][3][4][5]. Presently, the subject of nonstandard seating positions has been relatively rarely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Seat position tendencies depend mainly on the age of the occupants and whether the front or rear seats are considered [1,[6][7][8][9][10]. It has been found that a partially reclined seat is pre-dominant while a full reclined position constitutes a small proportion of cases.…”
Section: Introductionmentioning
confidence: 99%